Between myth and mate: medical skills and postmodernism - Armenteros, Víctor M. (2012)
Through the different moments of history display method has changed. Today theclash between modernity and modernity solid liquid (Postmodernism) continuesaltering concepts and valuations. This paper reflects from a dialogic platform of theissues raised at the time of the development of medical expertise from the impactof postmodernism.